Creative Economy-Based Community Empowerment in Tourism Villages: An Integrated Model from Indonesia - Ahnaf Nabil Rusnarasyid; Sujarwo Sujarwo; Yudan Hermawan (Papanda Publisher, 2026)
This study examines creative economy-based community empowerment in tourism villages, analyzing current conditions, influencing factors, income impacts, and formulating an effective empowerment model. Employing a qualitative case study design, data were collected through in-depth interviews, observations, and documentation involving 13 informants from Tepus and Gari Tourism Villages in Gunungkidul Regency, Indonesia. Data validity was ensured through triangulation, and analysis utilized the Miles, Huberman, and Saldaña interactive model. Results reveal that empowerment has evolved contextually, positioning communities as primary development subjects engaged in homestay management, tour guiding, handicraft production, and cultural performances. Supporting factors include government policies, institutional presence, social capital, and local resources, while barriers encompass limited human resource quality, digital literacy gaps, capital constraints, and weak institutional coordination. Creative economy initiatives generated gradual income increases, livelihood diversification, and flexible employment opportunities, particularly for women and youth, though benefit distribution remains uneven. The study formulates an integrated empowerment model comprising three pillars: institutional strengthening and inter-actor synergy, needs-based training and mentoring, and digital technology integration. This model extends community-based tourism literature by demonstrating how non-formal education, asset mobilization, and collaborative governance can be operationalized in rural contexts, offering practical guidance for designing context-specific interventions that strengthen community agency while addressing structural constraints.